MAKNA RESIPROSITAS TRADISI MBECEK PADA PEREMPUAN PEDESAAN JAWA DALAM ACARA PERNIKAHAN DI BANYUANGI JAWA TIMUR, INDONESIA - Eko Setiawan (Pusat Studi Gender dan Anak, 2022)
The mbecek tradition was born from the womb of solidarity of the people of Kalipait Village as a complete emotional bond. It has been a tradition for generations. The exciting thing about this research is that the mbecek tradition is an ancestral heritage that until now has remained sustainable due to cultural and social factors. As times have changed, the tradition of mbecek used to be based on the principle of helping but now experiencing a shift in business mixed with business is felt to be burdensome. Allows for the occurrence of family economic resistance. This research was conducted to determine the meaning of reciprocity of the mbecek tradition of Javanese rural women. This research uses a qualitative research method with a descriptive approach—data collection through observation, in-depth interviews, and documentation. Data analysis using an interactive model begins by continuously examining all data from primary and secondary sources until the data is saturated. The results showed that mbecek is a vehicle for exchange in the form of money and staples as a form of investment to maintain kinship ties.